2022
DOI: 10.1037/prj0000513
|View full text |Cite
|
Sign up to set email alerts
|

Personal recovery in the postdischarge period for individuals with schizophrenia spectrum diagnoses: The role of community integration and social support.

Abstract: Objective: The experience of personal recovery from mental health has been theorized to occur through several pathways. CHIME is a seminal theoretical framework of personal recovery that is widely endorsed by the existing literature. Few studies have examined the utility of the CHIME framework with those experiencing acute challenges in their engagement in the recovery process. The purpose of the present study was to examine part of the CHIME framework for individuals with schizophrenia spectrum diagnoses in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The sample size needed for serial mediation was calculated using the Monte Carlo Power Analysis webpage (Schoemann et al., 2017). Referencing the correlation coefficients reported in previous studies, the correlation coefficients between self‐stigma and social support, between self‐stigma and perceived hope, between self‐stigma and perceived recovery, between social support and perceived hope, between social support and perceived recovery, and between perceived hope and perceived recovery were set to −.353 (Li et al., 2021), −0.582 (Lim et al., 2020), 0.560 (Lim et al., 2020), 0.219 (Mutschler et al., 2022), and 0.641 (Sari et al., 2021), respectively; referencing previous relevant studies that used the tools expected to be employed in this study, the standard deviations for self‐stigma, social support, perceived hope and perceived recovery were set to 10.83 (Lin et al., 2022), 15.48 (Prabhakaran et al., 2021), 5.02 (Lim et al., 2020), and 9.04 (Yang & Lo, 2017), respectively. The calculation by the webpage indicated that when the sample size was 110, the power was 0.97.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size needed for serial mediation was calculated using the Monte Carlo Power Analysis webpage (Schoemann et al., 2017). Referencing the correlation coefficients reported in previous studies, the correlation coefficients between self‐stigma and social support, between self‐stigma and perceived hope, between self‐stigma and perceived recovery, between social support and perceived hope, between social support and perceived recovery, and between perceived hope and perceived recovery were set to −.353 (Li et al., 2021), −0.582 (Lim et al., 2020), 0.560 (Lim et al., 2020), 0.219 (Mutschler et al., 2022), and 0.641 (Sari et al., 2021), respectively; referencing previous relevant studies that used the tools expected to be employed in this study, the standard deviations for self‐stigma, social support, perceived hope and perceived recovery were set to 10.83 (Lin et al., 2022), 15.48 (Prabhakaran et al., 2021), 5.02 (Lim et al., 2020), and 9.04 (Yang & Lo, 2017), respectively. The calculation by the webpage indicated that when the sample size was 110, the power was 0.97.…”
Section: Methodsmentioning
confidence: 99%